Epidemiological association between multiple chemical sensitivity and birth by caesarean section: a nationwide case-control study - Kentaro Watai; Yuma Fukutomi; Hiroaki Hayashi; Yosuke Kamide; Kiyoshi Sekiya; Masami Taniguchi (BMC, 2018)
Abstract Introduction Multiple chemical sensitivity (MCS) is characterized by recurrent nonspecific symptoms that are attributed to exposure to trace levels of environmental agents. Although the clinical symptoms of MCS have been described in several studies, the risk factors for this condition remain unclear. Our aim was to clarify the risk factors for MCS and the association between MCS and birth by caesarean section. Methods We conducted a nationwide case-control study of Japanese individuals (aged 20-65 years) with physician-diagnosed MCS (183 cases) and without MCS (345 controls). The study participants were selected from among 150,000 people in a web-based research panel with approximately 1,000,000 registrants. They completed an online survey including questions on their sociodemographic characteristics, birth history (i.e., birth by caesarean section), and other potential risk factors for MCS. Multivariate logistic regression analysis was employed to determine the association between sociodemographic characteristics and the risk of MCS. Results The proportions of case and control subjects who were born by caesarean section were 39.9 and 7.0%, respectively. The association between birth by caesarean section and MCS was significant even after adjusting for potential confounders (adjusted odds ratio: 6.15; 95% confidence interval: 3.13-12.1). A history of agricultural work, mouth breathing, ≥11 vaccinations in the past 10 years, and residing in a new home (< 1 year-old) ≥3 times were also significantly associated with MCS. Conclusion Our data indicate an epidemiological link between MCS and birth by caesarean section. Moreover, we show that factors other than chemical exposure may be associated with the development of MCS.